Molecular, biochemical and metabolomics analyses reveal constitutive and pathogen-induced defense responses of two sugarcane contrasting genotypes against leaf scald disease - Bini, Andressa Peres; Rossi, Guilherme Duarte [UNESP]; Poeschl, Yvonne; Serra, Marina Carnaz Duarte; Camargo, Luis Eduardo Aranha; Monteiro-Vitorello, Claudia Barros; van Sluys, Marie-Anne; van Dam, Nicole M.; Uthe, Henriette; Creste, Silvana (Elsevier, 2023)
Leaf scald caused by the bacteria Xanthomonas albilineans is one of the major concerns to sugarcane production. To breed for resistance, mechanisms underlying plant-pathogen interaction need deeper investigations. Herein, we evaluated sugarcane defense responses against X. albilineans using molecular and biochemical approaches to assess pathogen-triggered ROS, phytohormones and metabolomics in two contrasting sugarcane genotypes from 0.5 to 144 h post-inoculation (hpi). In addition, the infection process was monitored using TaqMan-based quantification of X. albilineans and the disease symptoms were evaluated in both genotypes after 15 d post-inoculation (dpi). The susceptible genotype presented a response to the infection at 0.5 hpi, accumulating defense-related metabolites such as phenolics and flavonoids with no significant defense responses thereafter, resulting in typical symptoms of leaf scald at 15 dpi. The resistant genotype did not respond to the infection at 0.5 hpi but constitutively presented higher levels of salicylic acid and of the same metabolites induced by the infection in the susceptible genotype. Moreover, two subsequent pathogen-induced metabolic responses at 12 and 144 hpi were observed only in the resistant genotype in terms of amino acids, quinic acids, coumarins, polyamines, flavonoids, phenolics and phenylpropanoids together with an increase of hydrogen peroxide, ROS-related genes expression, indole-3-acetic-acid and salicylic acid. Multilevel approaches revealed that constitutive chemical composition and metabolic reprogramming hampers the development of leaf scald at 48 and 72 hpi, reducing the disease symptoms in the resistant genotype at 15 dpi. Phenylpropanoid pathway is suggested as a strong candidate marker for breeding sugarcane resistant to leaf scald.
Keywords: Monocots disease; Pathogen-induced resistance responses; Phytohormones; Plant metabolomics; ROS